A new species of Moenkhausia Eigenmann (Characiformes: Characidae) from the rio Arinos basin, Brazil - Fernando C. P. Dagosta; Manoela M. F. Marinho (Neotropical Ichthyology)
ABSTRACT A new species of Moenkhausia is described from the rio Arinos drainage, rio Tapajós basin, Mato Grosso, Brazil. The new species is diagnosed from all congeners, except M . hemigrammoides , M . nigromarginata , and Moenkhausia rubra by having intense diffuse dark pigmentation on the dorsal and anal fin-rays. The new species can be distinguished from the above mentioned species by the combination of 20-23 branched anal-fin rays, presence of a vertically elongate roughly rectangular humeral spot surpassing the lateral line ventrally, absence of a well-defined black spot on the distal portion of the dorsal fin and lack of a series of longitudinal dark zigzag stripes on body. The new species is herein described along with a report and discussion of a possible connection between the rio Tapajós and rio Paraguay basins, near Diamantino Municipality, Mato Grosso.